Analysis of the Influence of Quality Work Of Life on the Intention To Leave Nurses at XYZ Sidoarjo Hospital - Budhi Setianto; Unsiyah Zulfa Ulinnuha (Universitas Nahdlatul Ulama Surabaya, 2026)
One of the serious challenges currently faced by XYZ Hospital in Sidoarjo, a class C hospital, is the employee turnover rate which continues to increase significantly. The increasing number of employee transfers and resignations has become a critical internal concern, as the turnover rate has exceeded the hospital management’s established threshold of 5%. field conditions indicate that this threshold has been surpassed over the past several periods. The objective of the study was to analyze the effect of Quality of Work Life (QWL) on nurses' intention to leave, in order to understand how various aspects of the work environment influence nurses’ tendency to resign, and to provide a basis for developing effective nurse retention strategies within the hospital. This observational study employed a cross-sectional design, in which researchers conducted observations without providing any intervention on the variables under study. A total of 182 participants were selected from a population of 402 employees using the Slovin formula, followed by simple random sampling. Located at XYZ Hospital in Sidoarjo. Data analysis was conducted using simple linear regression to examine the causal relationship between the independent variable, Quality of Work Life (QWL), and the dependent variable, intention to leave. Quality of Work Life was measured through three dimensions: job satisfaction, organisational culture, and work climate. A relationship was considered statistically significant if the significance value (p-value) was less than 0.05. Based on the results of the study conducted at XYZ Hospital, Quality of Work Life—encompassing organisational culture, work climate, and job satisfaction—was found to be at a moderate level. Similarly, employees’ intention to leave was also categorised as moderate. The regression analysis demonstrated that Quality of Work Life had a significant effect on intention to leave. These findings indicate that higher perceived Quality of Work Life is associated with a lower tendency among employees to leave the organisation. Keywords: Organizational Culture, Intention To Leave, Quality Work Of Life, Job Satisfaction